Microneedle assisted micro-particle delivery by gene guns: Mathematical model formulation and experimental verification. (24th March 2015) - Zhang, Dongwei; Das, Diganta B.; Rielly, Chris D.
Abstract: Gene gun is a micro-particles delivery system which accelerates DNA loaded micro-particles to a high speed so as to enable penetration of the micro-particles into deeper tissues to achieve gene transfection. Previously, microneedle (MN) assisted micro-particles delivery has been shown to achieve the purpose of enhanced penetration depth of micro-particles based on a set of laboratory experiments. In order to further understand the penetration process of micro-particles, a mathematical model for MN assisted micro-particles delivery is developed. The model mimics the acceleration, separation and deceleration stages of the operation of a gene gun (or experimental rig) aimed at delivering the micro-particles into tissues. The developed model is used to simulate the particle velocity and the trajectories of micro-particles while they penetrate into the target. The model mimics the deceleration stage to predict the linear trajectories of the micro-particles which randomly select the initial positions in the deceleration stage and enter into the target. The penetration depths of the micro-particles are analyzed in relation to a number of parameters, e.g., operating pressure, particle size, and MNs length. Results are validated with experimental results obtained from the previous work. The results also show that the particle penetration depth is increased from an increase of operating pressure, particle size and MN length. The presence of the pierced holes causes a surge in penetration distance. Highlights: Microneedle (MN) assisted micro-particle delivery enhances particle penetration. Mathematical model for MN assisted micro-particles delivery is developed. Results are validated with experimental results obtained from the previous work. Developed model is used to simulate velocity and trajectories of micro-particles. MNs assist in reducing operating pressures for gene guns.